New Non-invasive Techniques to Quantify Skin Surface Strain and Sub-surface Layer Deformation of Finger-pad during Sliding. (December 2017) - Liu, X.; Maiti, R.; Lu, Z.H.; Carré, M.J.; Matcher, S.J.; Lewis, R.
Abstract: Studies on the variation of skin properties with gender, age and anatomical region, with regards to interaction with different materials have resulted in significant research output. Investigations on skin surface strain and sub-surface layer deformation during sliding, however, have not received as much attention. This novel study uses two non-invasive techniques, optical coherence tomography (OCT) and digital image correlation (DIC), to measure properties of the index finger of a 25 year old female when under normal and shear loading. Measurements were taken during static, and for the first time, dynamic phases. It was observed that the number of ridges in contact with a Quartz glass surface, observed under OCT, reduced when the finger started sliding. The sliding also resulted in deformation at the stratum corneum junction. The surface strain, analysed using DIC was higher nearer to the distal interphalangeal joint compared to the fingertip. This newly developed approach provides a powerful and non-invasive method to study the structural changes of finger-pad skin during loading and sliding. This approach can now be repeated at different anatomical locations for medical, bioengineering and consumer applications. Highlights: Surface strain and sub-surface deformation quantified using OCT and DIC. Finger-pad ridges in contact with a Quartz glass surface, observed under OCT, reduced when the finger started sliding. The sliding also resulted in deformation at the stratum corneum-epidermis junction. The surface strain, analysed using DIC was higher nearer to the distal interphalangeal joint compared to the fingertip.